KOMPOSISI KIMIA TEPUNG KECAMBAH JAGUNG DAN TEPUNG KECAMBAH KEDELAI (KEJALE) TERGRANULASI - Siti Aminah; Budi Santoso (Universitas Muhammadiyah Semarang, 2014)
A mixture of corn and soybeans have a good effect on the complementation of protein qualityimprovement. The nutritional value of corn and soybeans can be improved through germination.Sprouts in the form of fresh have perishable characteristics and limited consumption. Onealternative utilization of corn sprouts and soy sprouts are product development in the form ofgranules. This study aimed to obtain the optimum chemical composition of corn germ flourtreatment formulations and flour soybean sprouts (kejale) granulated. The results showed thatthere was a treatment effect of formulation ingredients on fat content, protein, carbohydrate, andcrude fiber. The ratio of soybean sprouts powdery material which causes higher levels of fat andprotein were higher. Meanwhile, the higher the proportion of carbohydrate ingredients flourcorn sprouts are higher.Keyword: granule, corn sprouts, soy sprouts